A randomised controlled trial to compare the efficacy of an aluminium lactate/potassium nitrate/hydroxylapatite toothpaste with a control toothpaste for the prevention of dentine hypersensitivity. (May 2021) - Seong, Joon; Newcombe, Robert G.; Foskett, Helen L.; Davies, Maria; West, Nicola X.
Abstract: Objectives: To determine the efficacy of a cosmetic aluminium lactate/potassium nitrate/hydroxylapatite toothpaste for the reduction of dentine hypersensitivity (DH) pain as compared to a control toothpaste containing potassium nitrate. Methods: The study was a randomised, examiner-blind, two treatment arm, parallel controlled trial in healthy adults with at least 2 sensitive teeth (Schiff > 2). At baseline, immediately after treatment and at 7 and 14 days of twice-daily brushing of the test or control toothpaste the sensitivity of 2 test teeth was measured following iced-water (Schiff and VAS) and tactile (Yeaple probe) stimuli, and a whole mouth plaque score was obtained. Participants also completed a whole-mouth VAS and DHEQ15 quality of life questionnaire at baseline, 7 and 14 days. Results: Both toothpastes reduced DH in test teeth, but pain reduction in the test group was significantly better at all timepoints and by all measures (p = 0.005, tooth-level VAS immediately after brushing; p < 0.001 all other comparisons). There was a relative risk reduction of Schiff sensitivity of 55 % immediately after brushing which rose to 81 % after 7 and 88.6 % after 14 days (all p < 0.001). There were no differences in plaque, whole mouth VAS or DHEQ15 scores at any time point. Conclusion: This study demonstrated the efficacy of an aluminium lactate/potassium nitrate/hydroxylapatite toothpaste compared to a potassium nitrate control toothpaste for the prevention of dentine hypersensitivity both immediately and over a 2 week period. This agent appears to have potential for pain alleviation from the common oral pain condition of DH and further research is warranted. Clinical significance: DH pain, whilst transient in nature, is arresting in magnitude, affecting quality of life. Daily application of efficacious toothpastes can relieve DH pain however, as yet, there is no gold standard treatment. The results of this study support further investigation of an aluminium lactate/potassium nitrate/hydroxylapatite toothpaste for DH management.